Study of Floristic Composition of Arnica Montana L. Grasslands Exploited Low-Input - ROTAR, Ioan; PĂCURAR, Florin; VIDICAN, Roxana; BOGDAN, Anca; DEAK, Denes; BANTO, Erika (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Agriculture, 2012)
In sustainable view and given the new climate and demographic phenomena, the mountains must be a clean living environment, supplier of energy, biodiversity and food for humans and animals, adequate safety measures and good management, with continued compliance with the balance agroforestry and preventing human depopulation and agricultural traditions and cultural degradation. Oligotrophic grasslands from Gârda de Sus village was a subject of Arnica Project (2004-2007, www.arnica-montana.ro). This project aimed at sustainable exploitation of Arnica montana L. species benefit and welfare of local people. So, oligotrophic grasslands have managed so as to maintain the species Arnica montana L. in abundance-dominance as possible. Following this project was set into remote exploit local species Arnica montana L. and that capitalize on the international market as certified product. Interests of entrepreneurs are to maintain the existing flora in the oligotrophic meadows. The obiective of our study is to evaluate the effect of low-inputs on a grassland of Arnica montana  L. from boreal floor, Gârda de Sus, Apuseni Mountains, Romania. In Apuseni Mountains, extensive grazing and extensive meadow management practices have been typically for subsistencebased or small-scale farming systems in areas of low agriculture productivity. However, longer term effects of these grasslands need to be investigated.